2005
DOI: 10.1152/ajpheart.00733.2004
|View full text |Cite
|
Sign up to set email alerts
|

Atrial contractile dysfunction, fibrosis, and arrhythmias in a mouse model of cardiomyopathy secondary to cardiac-specific overexpression of tumor necrosis factor-α

Abstract: . Atrial contractile dysfunction, fibrosis, and arrhythmias in a mouse model of cardiomyopathy secondary to cardiac-specific overexpression of tumor necrosis factor-␣. Am J Physiol Heart Circ Physiol 289: H1456 -H1467, 2005. First published May 27, 2005; doi:10.1152/ajpheart.00733.2004.-Transgenic mice overexpressing the inflammatory cytokine TNF-␣ in the heart develop a progressive heart failure syndrome characterized by biventricular dilatation, decreased ejection fraction, decreased survival compared with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
109
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 49 publications
4
109
1
4
Order By: Relevance
“…Indeed, studies in Cx40-deficient mice are consistent with the electrical phenotype observed in our MHCsTNF mice, including depressed sinus node activity, increased AV Wenckebach periodicity, increased inducibility of atrial tachyarrythmias, and reduced conduction in the His-Purkinje system with preserved conduction velocity in the ventricular myocardium (4,12,30,35,36). Our results of atrial arrhythmias in a mouse model with overexpression of TNF confirm previous observations by others (27). However, a novel finding of our study was the role of Cx40 in the setting of inflammation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, studies in Cx40-deficient mice are consistent with the electrical phenotype observed in our MHCsTNF mice, including depressed sinus node activity, increased AV Wenckebach periodicity, increased inducibility of atrial tachyarrythmias, and reduced conduction in the His-Purkinje system with preserved conduction velocity in the ventricular myocardium (4,12,30,35,36). Our results of atrial arrhythmias in a mouse model with overexpression of TNF confirm previous observations by others (27). However, a novel finding of our study was the role of Cx40 in the setting of inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…However, a novel finding of our study was the role of Cx40 in the setting of inflammation. Furthermore, while myocardial tissue fibrosis was evident in TNF mice aged 2-9 mo (27), it is unlikely that fibrosis played a major role in the pathogenesis of atrial arrhythmias in our model, insofar as fibrosis does not develop significantly in this model until 12 wk of age (32). Ion channel currents are altered in heart failure; specifically, it is thought that L-type calcium currents are upregulated and transient outward potassium currents are downregulated (14).…”
Section: Discussionmentioning
confidence: 88%
“…TNF‐α has been demonstrated to induce atrial fibrosis by increasing atrial myofibroblast proliferation and metalloproteinase secretion 23, 24. Saba et al25 found that cardiac‐specific overexpression of TNF‐α could cause atrial contractile dysfunction, fibrosis, and arrhythmias in a mouse model. Moreover, a recent study has revealed that enhanced expression of TNF‐α in the murine atrial cardiomyocyte HL‐1 cell line promoted cardiomyocyte apoptosis by activating CASP‐3 26.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of 52 decompensated patients with cirrhosis, natriuretic peptide level correlated with the Child-Pugh score and the ventricular wall thickness (39). The mechanism of impaired cardiac function is complex and may include (1) neurohumoral hyperactivity leading to myocardium growth and fibrosis with disturbed relaxation; (2) diminished myocardial ␤ adrenergic receptor signal transduction; and (3) an inhibitory effect of circulating cytokines, including TNF-␣ and nitric oxide (NO), on ventricular function (37,40,41). In alcoholic patients, a variable degree of alcoholic cardiomyopathy also can be a contributing factor.…”
Section: Cardiac Dysfunctionmentioning
confidence: 99%